Trends in the global, national, and regional burden of breast cancer among adolescents and young adults from 1990 to 2021: Analyses of the 2021 global burden of disease study - Da Qian; Weimin Hong; Shujin Li; Haotian Liu; Chaoqi He; Xiaozhen Liu; Guoxin Huang; Xuli Meng; Yiwen Zheng (Breast)
Background: This study was devised to evaluate the burden of breast cancer (BC) among adolescents and young adults (AYAs) between 1990 and 2021. Methods: BC burden among AYAs (15–39 years of age) was analyzed by examining the associated age-standardized incidence rate, age-standardized prevalence rate, age-standardized death rate, and age-standardized disability-adjusted life year (DALY) rates between 1990 and 2021 at the global, national, and regional levels, together with corresponding analyses of health inequality and decomposition analyses. Results: In 2021, the respective global age-standardized incidence rate, age-standardized prevalence rate, age-standardized death rate, and age-standardized DALYs for BC were 5.87 (5.39,6.41), 49.35 (45.46,53.86), 1.37 (1.24,1.51), and 80.8 (72.84,89.23), which respectively showed increases of 33.4 %, 35.2 %, 1.5 %, and 3.3 % compared to the rate of 1990. While women comprise the vast majority of all BC cases, a higher average annual percent change was observed for males relative to females at the global level. The average annual percent change for BC incidence, prevalence, death, and DALYs among men AYAs (2.59, 2.49, 1.06, 1.10) were all higher than the corresponding values among women (0.91, 0.96, 0.02, 0.09). Regional and national differences in disease burden were observed. BC disease burden was significantly positively correlated with socio-demographic index (SDI). Similar trends were observed in terms of female disease burden, whereas disease burden of male patients was negatively related to SDI. In decomposition analyses, the primary factors associated with changes in age-standardized DALY rates were identified as aging and population growth. Health inequality analyses revealed that the burden of BC among AYAs was particularly concentrated in lower-income countries. Conclusions: These results highlight that the burden of BC among AYAs has grown in recent decades, while also emphasizing the need to be attentive to the rising occurrence of male BC. Lower-income regions also faced a heavier BC-related burden as compared to more affluent nations. Efforts to reduce the disease burden associated with BC may thus hinge on government-based initiatives focused on improving overall national economic strength and medical system quality.